(untitled) (Scientific journal of the Fergana State University, 2024)
The article says that many people are involved in the process of the digital communication, which has its own characteristics and differs from the literary language and live speech. This new phenomenon in most cases proceeds in writing with the use of non-verbal means. There is explained the used literatures in the literature review part of the article. The methodology part is given properly according to the requirements.